PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA - Fefen, Zukruf (Departemen Matematika, 2023)
Understanding the concept is one of the goals in mathematics lessons. However, in reality the ability of class XI MIPA MAN 2 Payakumbuh students is still low. This is as a result of the teacher-centered nature of the educational process. The learning process has not actively involved students. The application of cooperative learning type Student Teams Achievement Division (STAD) is one way to overcome this problem. The purpose of this research was to analyze and describe students' understanding of mathematical concepts during the application of the STAD learning model and the conventional model. This research used the Nonequivalent Posttest-Only Group Design and the quasi-experimental method. The findings of this study indicate that the use of the STAD model further enhances this ability compared to using conventional learning models. Keywords– Conventional Model, Cooperative Learning, Students Teams Achievement Division, Understanding Mathematical Concept.